Optimalisasi Tempat Penyimpanan Limbah Bahan Berbahaya dan Beracun Rumah Sakit Umum Daerah Karawang - Septiany, Deby; Sari, Gina Lova; Bunga, Venny Ulya (Al-Ard: Jurnal Teknik Lingkungan, 2025)
Karawang Regional Public Hospital faces an increase in hazardous waste production due to an increase  in the number of patients and health services up to nine percent. The hazardous waste is no longer accomodated by their hazardous storage in the size of 8.00 x 3.00 m. The objective of the current study is to optimize the hazardous waste storage by rearranging the packaging and layout of the hazardous waste storage following the Minister of Environment Forestry Regulation No. 56 of 2015 and the Minister of Environment Forestry Regulation No. 6 of 2021. This research is a descriptive study using a qualitative approach. Hazardous waste production data is collected by sampling for eight days in accordance with Indonesian National Standard No. 19-3964-1994. Meanwhile, information about existing management and policies of hazardous waste at Karawang Regional Public Hospital were collected through observation and interview. The results showed that the average daily production of hazardous waste was 291.13 kg; 22.36 kg; 4.18 kg; and 30.77 kg for infectious, sharps, cytotoxic, and liquid medical, respectively. The optimization steps for hazardous waste storage include improving packaging, rearranging the layout by utilizing vertical space, and increasing the frequency of transportation by licensed transporter. The implementation of these steps can assist the hospitals in improving the effectiveness, safety, and cost efficiency hazardous waste management.